Geometric properties of noninformative priors based on the chi-square divergence - Tanaka, Fuyuhiko (Frontiers in Applied Mathematics and Statistics, 2023)
Recently, a noninformative prior distribution that is different from Jeffreys prior has been derived as a certain extension of Bernardo's reference prior based on the chi-square divergence. We summarize the result in terms of information geometry and clarify some geometric properties. We show that it corresponds to a parallel volume element and it is written as a power of Jeffreys prior in flat model manifolds.